Self-Compassion dan Body Image Pada Mahasiswi Pengguna Instagram - Rizha Pera Maharani; Katrim Alifa Putrikita (Syiah Kuala Psychology Journal, 2024)
Instagram is used in various societies, including female college students. Instagram shows ideal body figures that influence how female students view their bodies. Body image refers to the perspective of a person towards their body shape, either positively or negatively. How individuals assess their body is associated with how individuals like themselves. Self-compassion is the caring and loving that is given to oneself, including accepting weaknesses and realizing that the experiences of others are also being endured. The purpose of this study is to examine the correlation between self-compassion and body image in female college student who use Instagram. This study uses quantitative methods with a correlational approach. The sampling technique used is purposive sampling, involving 200 female college student as Instagram users. Data were collected using self-compassion scale and body image scale. Data analysis was conducted with Pearson product moment correlation analysis. The results showed a positive relationship between self-compassion and body image among female Instagram users.Instagram digunakan di berbagai kalangan, termasuk mahasiswi. Instagram sering menampilkan figure tubuh ideal yang mempengaruhi bagaimana pandangan mahasiswi terhadap tubuhnya. Body image merujuk pada cara pandang seseorang terhadap bentuk tubuhnya, baik positif ataupun negatif. Bagaimana individu menilai tubuhnya ini kemudian dikaitkan dengan bagaimana individu mencintai dirinya sendiri. Self-compassion adalah perhatian dan kasih sayang yang diberikan terhadap diri sendiri, termasuk menerima kelemahan dan menyadari bahwa pengalaman yang dialami juga dialami oleh orang lain. Tujuan dari penelitian ini adalah untuk mengkaji hubungan antara self-compassion dan body image pada mahasiswi pengguna Instagram. Penelitian ini menggunakan metode kuantitatif dengan pendekatan korelasional. Teknik sampling yang diterapkan adalah purposive sampling, melibatkan 200 mahasiswi pengguna Instagram. Data dikumpulkan menggunakan skala self-compassion dan skala body image. Analisis data dilakukan dengan analisis korelasi product moment Pearson. Hasilnya menunjukkan adanya hubungan positif antara self-compassion dan body image di antara mahasiswi pengguna Instagram.